PREVENTION HUMAN TRAFFICKING THROUGH COMMUNITY WATCH - Juliana Susantje Ndolu; Helsina F.I Pello (Jurnal Pembaharuan Hukum, 2020)
This study aims to first determine the factors driving community involvement in Community Watch Human Trafficking and knowing the role of Community Watch Human Trafficking in the aspect of preventing human trafficking. The results of the study are as follows. First, the factors driving community involvement in CW-PO are: legal awareness of the dangers of trafficking in persons and their impacts; the experiences of family members and neighbors who have been victims of the Human Trafficking criminal act; accustomed to volunteering; There are joint concerns because there is an Indonesian Manpower Services Company and field workers who are tasked with recruiting prospective migrant workers from the village. Secondly, the role of Community Watch Human Trafficking in the prevention aspect of yatru: To collect data on migrating citizens; increasing public understanding of Human Trafficking criminal act; economic empowerment; advocating for village government to allocate village funds to open businesses; accompany former migrant workers who have returned to the village but have problems; carry out monitoring in the village.